Quantum Sensing, Imaging, and Precision Metrology 2023
DOI: 10.1117/12.2657192
|View full text |Cite
|
Sign up to set email alerts
|

Velocity‐modulated atom interferometry with enhanced dynamic range

Abstract: We present new modes of operation in a continuous, 3D-cooled atomic beam interferometer designed for inertial sensing. In these experiments, a moving optical molasses cooling stage provides both three-dimensional cooling and excellent dynamic control over atomic beam velocity. By modulating the atomic beam velocity, we modulate the interferometer scale factor, enabling us to extract the absolute inertial phase over many phase cycles without sacrificing short-term sensitivity. These demonstrations provide a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In past work, we have shown that temporal variation of the mean velocity of the atomic beam in our spatial-domain atom interferometer can provide a significant increase in dynamic range. 11 In this work, we demonstrate, through modeling and experiment, the mitigation of time-varying errors in atom interferometer phase through time-domain control of the direction of photon recoil in a spatial domain atom interferometer. Estimation and subtraction of systematic phase errors through reversal of the direction of photon recoil is a longstanding technique in atomic inertial sensing in both time-domain and spatial-domain atom interferometers.…”
Section: Introductionmentioning
confidence: 99%
“…In past work, we have shown that temporal variation of the mean velocity of the atomic beam in our spatial-domain atom interferometer can provide a significant increase in dynamic range. 11 In this work, we demonstrate, through modeling and experiment, the mitigation of time-varying errors in atom interferometer phase through time-domain control of the direction of photon recoil in a spatial domain atom interferometer. Estimation and subtraction of systematic phase errors through reversal of the direction of photon recoil is a longstanding technique in atomic inertial sensing in both time-domain and spatial-domain atom interferometers.…”
Section: Introductionmentioning
confidence: 99%